Legalitas Invasi Militer Terhadap Kedaulatan Teritorial Negara Dan Pertanggungjawabannya - Hetharie, Brandon Tanner; Kainama, Marthinus; Wattimena, Josina Augustina Yvonne (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Military invasion is the act of deploying a country's armed forces into the sovereign territory of another country with the aim of controlling, replacing the existing government, taking part of the territory and even helping the region to secede from its parent country. In reality, military invasions are often carried out, such as Russia's military invasion of Ukraine in 2022.Purposes of the Research:  The purpose of this study is to examine and find out the legality of military invasions against state territorial sovereignty and its responsibility.Methods of the Research: This research is a normative juridical research is a document study (using legal sources such as laws and regulations, court decisions, legal theories and / or opinions of scholars). In simple terms, this type of research is also called doctrinal legal research, literature or document studies.Results of the Research: The results of this study show that the legality of military invasion of a country's territorial sovereignty is not justified in international law. The regulation of military invasion is recognized as an act of aggression stipulated in article 3 of UN General Assembly Resolution 3314 and reinforced as a crime of aggression in article 8 bis paragraphs 1 and 2 of the Rome Statute. Military invasion is also a violation of a country's sovereignty based on the UN Charter article 2 paragraphs 1 and 4, Kellog-Briand pact, Declaration on Rights and Duties of States. If a military invasion leads to war, it must be subject to the provisions of jus war. The form of state responsibility for acts of military invasion of a country's territorial sovereignty is in the form of satisfaction (submission of a memorandum of apology) to the injured state followed by the withdrawal of armed forces with a guarantee that it does not repeat the action and makes compensation in the form of giving a sum of money or compensation is not a sum of money known as nonpecuniary.